THE EFFECT OF EVENT QUALITY TOWARDS SATISFACTION AND FUTURE INTENTION TO RETURN OF DBL SPECTATORS IN SURABAYA - GINNY SIDI, 041411231202 (2018)
Sports events have been growing in Indonesia, more competitions have been held, but not all competition succeed in attracting a lot of spectators to attend their event. This might cause by minimal knowledge about what affects the spectator’s satisfaction, what affects their intention to return again to the event, how to measure the event quality, and which event quality is the most important in Indonesia sports events. So, to give some insights in this field, this research tried to find the effect of event quality towards satisfaction and future intention to return of DBL spectators in Surabaya. Respondents of this research are spectators of DBL who have watched at least one game of DBL 2018 event in Surabaya from 24 April until 6 May 2018. This research used a quantitative approach which tests some hypothesis by using SEM PLS (Structural Equation Modelling Partial Least Square) analysis. This research used primary data by distributing online questionnaires through Line and Instagram for a week. The result of this research showed that event quality has a positive and significant relationship with both satisfaction and future intention to return. Satisfaction was found to have a bigger effect towards future intention than event quality. It was also found that physical environment quality is the most important dimension of event quality.